Cryovolcanism on Titan: New results from Cassini RADAR and VIMS. Issue 3 (19th March 2013) - Lopes, R. M. C.; Kirk, R. L.; Mitchell, K. L.; LeGall, A.; Barnes, J. W.; Hayes, A.; Kargel, J.; Wye, L.; Radebaugh, J.; Stofan, E. R.; Janssen, M. A.; Neish, C. D.; et al.
Abstract: [1] The existence of cryovolcanic features on Titan has been the subject of some controversy. Here we use observations from the Cassini RADAR, including Synthetic Aperture Radar (SAR) imaging, radiometry, and topographic data as well as compositional data from the Visible and Infrared Mapping Spectrometer (VIMS) to reexamine several putative cryovolcanic features on Titan in terms of likely processes of origin (fluvial, cryovolcanic, or other). We present evidence to support the cryovolcanic origin of features in the region formerly known as Sotra Facula, which includes the deepest pit so far found on Titan (now known as Sotra Patera), flow‐like features (Mohini Fluctus), and some of the highest mountains on Titan (Doom and Erebor Montes). We interpret this region to be a cryovolcanic complex of multiple cones, craters, and flows. However, we find that some other previously supposed cryovolcanic features were likely formed by other processes. Cryovolcanism is still a possible formation mechanism for several features, including the flow‐like units in Hotei Regio. We discuss implications for eruption style and composition of cryovolcanism on Titan. Our analysis shows the great value of combining data sets when interpreting Titan's geology and in particular stresses the value of RADAR stereogrammetry when combined with SAR imaging and VIMS. Key Points: Evidence to support volcanic origin of features on Titan Several Cassini data sets used to support the argument Sotra patera and associated features provide strongest evidence of cryovolcanism